2005
DOI: 10.1080/08038020500465809
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of blood‐pressure control in treated hypertensive patients in Croatia

Abstract: The aim of our study was to investigate blood pressure (BP) control and different factors with possible influence on BP control in Croatian hypertensive patients. In this cross-sectional investigation, a representative sample of target populations (primary care physicians and patients) from different parts of Croatia was included according to the study protocol. During December 2003 and January 2004, we included, according to correctly completed questionnaires, 141 physicians and 814 hypertensive patients. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…However, our results are generally consistent with the findings from recent European studies [46][47][48] and demonstrate an increase in the rate of achieving the targeted BP in Croatia when compared to the rate of 19.4% from the EH-UH study published in 2007 [49]. However, it has to be highlighted that in almost all of the aforementioned studies, study population included diabetic hypertensive patients [39,41,[44][45][46][47][48][49]. In a comparative study of three different European communities, England, Belgium and Italy, with diabetes mellitus as one of exclusion criteria, the rates of achieving normotension among those treated were 42.0, 43.0 and 47.7%, respectively [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our results are generally consistent with the findings from recent European studies [46][47][48] and demonstrate an increase in the rate of achieving the targeted BP in Croatia when compared to the rate of 19.4% from the EH-UH study published in 2007 [49]. However, it has to be highlighted that in almost all of the aforementioned studies, study population included diabetic hypertensive patients [39,41,[44][45][46][47][48][49]. In a comparative study of three different European communities, England, Belgium and Italy, with diabetes mellitus as one of exclusion criteria, the rates of achieving normotension among those treated were 42.0, 43.0 and 47.7%, respectively [50].…”
Section: Discussionsupporting
confidence: 91%
“…It is important to emphasize that our study addressed only patients with uncomplicated hypertension treatment. We excluded the patients with diabetes since it was shown to be associated with higher systolic and diastolic BP values [44] and a negative predictor of BP control [45]. The rates of achieving normotension were relatively high, compared to 32.5% of the patients receiving treatment and controlled in the international community-based Prospective Urban Rural Epidemiology (PURE) study [39].…”
Section: Discussionmentioning
confidence: 99%
“…occupation in low ranking workers, low level of education and low income, was associated with higher blood pressure. Moreover, the results of recent studies on hypertension confirmed the association of lower monthly income and the level of education with higher blood pressure, lower awareness and control of hypertension [32,33,34,35]. The greater prevalence of hypertension was also observed in other rural parts of Croatia and Romania [29,36], while the prevalence was lower in Spain [37].…”
Section: Discussionmentioning
confidence: 53%
“…Epidemiological studies performed in America (United States, Canada) and Europe indicate that control of hypertension is insuffi cient despite pharmacotherapy: hypertension control (ABP <140/90 mm Hg) varies from 8.3% to 42% in different countries (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The data from other published trials indicate that the level of ABP control in treated patients is lower than in the mentioned trial.…”
Section: Discussionmentioning
confidence: 74%